How does water-reliant industry affect groundwater systems in coastal Kenya? - Ferrer, N; Folch, A; Lane, M; Olago, D; Katuva, J; Thomson, P; Jou, S; Hope, R; Custodio, E (Elsevier, 2019)
The industrialization process taking place in Africa has led to an overall increase in groundwater abstraction in most countries in the continent. However, the lack of hydrogeological data, as in many developing countries, makes it difficult to properly manage groundwater systems. This study presents a real case study in which a combination of different hydrogeological tools together with different sources of information allow the assessment of how increased competition for water may be affecting groundwater systems by analysing the sustainability of new abstraction regimes under different real climatic condition (before, during and after La Niña 2016). The area where this approach has been applied is Kwale County (in Coastal Kenya) in a hydrogeological context representative of an important part of the east coast of the continent, where new mining and agriculture activities co-exist with tourism and local communities. The results show that the lack of aquifer systems data can be overcome, at least partly, by integrating different sources of information. Most of the time, water-reliant users collect specific hydrogeological information that can contribute to defining the overall hydrogeological system, since their own main purpose is to exploit the aquifer with the maximum productivity. Therefore, local community water usage, together with different stakeholder's knowledge and good corporate water management act as a catalyst for providing critical data, and allows the generation of credible models for future groundwater management and resource allocation. Furthermore, complementary but simple information sources such as in situ interviews, Google Earth, Trip Advisor and easy-to use analytical methods that can be applied in the African context as in many developing countries, and enables groundwater abstraction to be estimated and the sustainability of the aquifer system to be defined, allowing potential future risks to be assessed.